TECHNOLOGY-ENHANCED TEACHING: A REVOLUTIONARY APPROACH TO TEACHING ENGLISH AS A FOREIGN LANGUAGE - Alberth Alberth (TEFLIN, 2013)
The online course offerings have grown exponentially globally since the turn of the 21st century - be they as a primary mode of instruction or as a supplement to traditional face-to-face classroom instruction, and this phenomenon is most noticeable in higher education. More recently, the new technology has also been integrated into the English as a Foreign Language,henceforth called EFL, classrooms. This article argues that the notion of technology-enhanced language learning is not just an intriguing idea â it is a necessity, for it has a great potential to offer in facilitating the development of English language proficiency of EFL learners through computer-mediated communication. Additionally, it contends that the new technology can potentially address most, if not all, of the shortcomings inherent to the EFL classroom including, but not limited to, lack of exposure to the target language, lack of practice, and lack of learning resources. Theoretical implications of technology-enhanced language teaching and learning will also be explored.Â